2012
DOI: 10.5539/ijps.v4n4p1
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Mental Structures of Eighth-graders in Different Countries on the Basis of Fennema-Sherman Test

Abstract: The intended factor structure of attitude scales in TIMSS 2007 dataset (N > 240, 000) is totally unstructured in several countries. There are two inseparable phenomena which explain the differences between countries. First, the ability level of the students is strictly connected with the level of maturation in thinking. Second, there are differences between countries which cannot be explained by the differences in achievement level. Four distinguishmental structures are identified: "Western" structure, "Africa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2015
2015

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Though the dimensions are the same, the item-wise changes are so radical that the Finnish test is no more Fennema-Sherman test but rather "loosely based on Fennema-Sherman test" as described by Metsämuuronen (2009, p. 20). Further, Metsämuuronen (2012a;2012b) argues, on the basis of extensive study with TIMSS dataset, that the Finnish version would be more suitable in the international settings because it is evident that the original test is not optimal with the lowest achieving students (Metsämuuronen 2012a) and in many Asian countries (Metsämuuronen, 2012b).…”
Section: Test Instruments and Their Reliabilitiesmentioning
confidence: 99%
“…Though the dimensions are the same, the item-wise changes are so radical that the Finnish test is no more Fennema-Sherman test but rather "loosely based on Fennema-Sherman test" as described by Metsämuuronen (2009, p. 20). Further, Metsämuuronen (2012a;2012b) argues, on the basis of extensive study with TIMSS dataset, that the Finnish version would be more suitable in the international settings because it is evident that the original test is not optimal with the lowest achieving students (Metsämuuronen 2012a) and in many Asian countries (Metsämuuronen, 2012b).…”
Section: Test Instruments and Their Reliabilitiesmentioning
confidence: 99%
“…For example, Metsämuuronen ( 2012a ), and Rutkowski and Rutkowski ( 2010 ) reported that some scales (e.g., math self-concept) that had been used in PISA and TIMMS studies showed less reliable scores in East Asia, the Middle East, and Europe, when compared to data from North America, where the scales were originally constructed. Metsämuuronen ( 2012b ) found that in the TIMSS2007, the math attitudes scale were not invariant and manifested " fragmentation " in most of the participating countries (in most low achieving countries) due to different cultural values. With empirical examples, Rutkowski and Rutkowski ( 2010 ) found that the possible cause to this was too much missing data: a possible sign of respondent misinterpretation.…”
Section: Theoretical Backgroundmentioning
confidence: 96%